The Influence of Transformational Leadership and Adversity Quotient on Teachers' Organizational Citizenship Behavior - Ariyanto, Ariyanto; Fuad, Nurhattati; Muhab, Sukro (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to analyze the influence of Transformational Leadership (TL) on Organizational Citizenship Behavior (OCB), the influence of Adversity Quotient (AQ) on teachers' Organizational Citizenship Behavior (OCB), and the influence of Transformational Leadership (TL) on Adversity Quotient (AQ) of state high school teachers in Kalideres sub-district, West Jakarta. This study takes a casual quantitative approach while using the survey method. Data collection, namely employing a questionnaire that the teacher who served as the responder responded to directly, primary data source comes from school principals in Ponorogo district, to obtain data related to teacher management that has been carried out and existing constraints. The population in this study were civil servant teachers at State Senior High School, Kalideres District, West Jakarta City for the 2021/2022 Academic Year, a total of 167 teachers. The samples taken were 118 teachers. The sampling technique of this study used simple random sampling. The results of the study show that: t (1) Transformational leadership has a direct positive effect on organizational citizenship behavior (OCB). In other words, good transformational leadership can increase organizational citizenship behavior. (2) The adversity quotient has a positive direct effect on organizational citizenship behavior (OCB). That is, a good adversity quotient can increase organizational citizenship behavior (OCB). (3) Transformational leadership has a positive direct effect on the adversity quotient. That is, good transformational leadership can increase the adversity quotient.